2010
DOI: 10.1016/j.jcis.2009.10.031
|View full text |Cite
|
Sign up to set email alerts
|

A study of competitive adsorption of organic molecules onto mineral oxides using DRIFTS

Abstract: Analysis of DRIFTS spectra was used for a quantitative study of competitive adsorption of myristic and salicylic acids onto kaolinite or γ-alumina. Peaks unique to the ring or the chain were selected and single molecule studies used as calibration. Samples were exposed to hexane solution containing equal molecular quantities of each acid. The surface loading of salicylic acid was not influenced by the presence of myristic acid on either mineral but the maximum loading of myristic acid was decreased (46 -50 %) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Adsorptive interactions between soil minerals and organic compounds are governed by mineral surface structural and charge properties, chemical properties of the organic compounds, solution chemistry (pH, ionic strength and composition) and the presence of competing organic or inorganic compounds (Thomas & Kelley, ; Zhang et al ., ). Many studies have shown that soil minerals can preferentially bind aromatic compounds, thus increasing their turnover time in soil (Kaiser & Guggenberger, ; Kalbitz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorptive interactions between soil minerals and organic compounds are governed by mineral surface structural and charge properties, chemical properties of the organic compounds, solution chemistry (pH, ionic strength and composition) and the presence of competing organic or inorganic compounds (Thomas & Kelley, ; Zhang et al ., ). Many studies have shown that soil minerals can preferentially bind aromatic compounds, thus increasing their turnover time in soil (Kaiser & Guggenberger, ; Kalbitz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has focused on the competitive adsorption between carboxylate and phosphate (sulfate), , two carboxylates, , as well as carboxylate and metal ions. , However, limited knowledge is available for competition mechanisms between carboxylate and phenolic aromatic compounds, especially on the microscopic level. The functional groups determine, in a large extent, the adsorption behaviors of the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the collected FTIR spectra of the untreated cotton and cotton–MBA–Cl. In the spectrum of cotton–MBA–Cl, the peaks at 2926 and 2854 cm –1 (corresponding to the symmetric and asymmetric stretching vibration of the C–H bonds on −CH 2 –CH 2 −) became stronger because the −CHCH– double bonds in MBA became −CH 2 CH 2 – after it was grafted onto cotton (as we can see in Figure ). The new peak at 1458 cm –1 corresponds to the in-plane bending vibration of the C–H bonds on −CH 2 –CH 2 –, which also demonstrated that the −CH 2 –CH 2 – became greater, and the new peak at 1281 cm –1 ascribes to the C–N vibrational bond .…”
Section: Results and Discussionmentioning
confidence: 86%